Social trust and the support for universal basic income - Michele Gubello (University College Dublin, UCD School of Economics, 2023)
This paper presents a theoretical model showing how political mistrust affects people's preferences for Universal Basic Income (UBI) when its implementation involves a reduction in spending for other public services (welfare retrenchment). The model shows that individuals with lower levels of political mistrust are more likely to endorse UBI, reflecting their trust in the government's ability to manage public resources and avoid wasteful retrenchment of other public services. The model also shows that generalised mistrust - characterized by agents' expectations of their fellow citizens' misbehaviour that can reduce the government's fiscal capacity- does not significantly influence preferences for UBI when it involves a partial retrenchment of other public services. This result is driven by the agents' perception that their fellow citizens' misbehaviour would occur irrespective of the UBI implementation. The empirical analysis with 265 European regions from the European Social Survey (ESS) confirms the predictions of the model.
Keywords: D7; H53; I38; 330; Universal Basic Income; Generalised Trust; Political Trust; Welfare Retrenchment